Role of HbA1c as a Marker of Dyslipidemia in Patients with Type 2 Diabetes Mellitus Visiting Tertiary Health Care Center - Rayamajhi, Prachi; Pradhananga, Salina; Mohan Bhattarai, Arabinda (Medical Journal of Shree Birendra Hospital, 2023)
Introduction: Diabetic patients with accompanied (but often unnoticed) dyslipidemia are soft targets of cardiovascular deaths. Glycated hemoglobin (HbA1c) is a routinely used marker for long-term glycemic control. This investigation is an attempt to evaluate the diagnostic value of HbA1c in predicting diabetic dyslipidemia. Methods: This was a cross-sectional study where the sera were analyzed for HbA1c, fasting blood glucose (FBG), total cholesterol, triglycerides, highdensity lipoprotein cholesterol (HDL) and low-density lipoprotein cholesterol. SPSS version 23.0 was used to analyze the data. Results: The levels of HbA1c did not differ significantly between males and females whereas male patients had significantly higher fasting blood glucose than females. There was a highly significant correlation between HbA1c and FBG. Both HbA1c and fasting blood glucose exhibited direct correlations with cholesterol, TG and LDL and inverse correlation with HDL; the magnitude of significance for all these lipid parameters being greater with HbA1c than fasting blood glucose. Conclusions: HbA1c can provide valuable information about the circulating lipids beside its primary role in monitoring long term glycemic control.